Multi-Strategy Self-Healing Approach for Stabilizing Ui Test Automation in Enterprise Crm Platforms with Dynamic Dom Architectures - Shkliar, Kostiantyn (Global Prosperity, 2026)
Browser-based test automation in enterprise CRM platforms suffers from persistent instability caused by dynamic DOM structures, encapsulated component architectures, and asynchronous rendering cycles. Industry data indicates that selector-related failures account for approximately 28% of test flakiness, while timing issues, data state mismatches, and incomplete rendering collectively produce the remaining 72%, a distribution that single-strategy healing tools fail to address. This paper presents a multi-strategy self-healing module that classifies each UI test failure by root cause before selecting a remediation path. Three coordinated mechanisms operate within the module: a Shadow DOM-aware element fingerprinting algorithm that resolves locator drift through composite attribute matching, an adaptive retry engine calibrated to platform-specific component lifecycle signals, and a failure classification layer that routes each detected anomaly to the appropriate healing strategy. Evaluated over six release cycles within a financial services CRM environment, the module reduced the UI-specific flakiness rate from 23% to under 3% and decreased the mean time to restore a failing scenario from 35 minutes of manual investigation to under 90 seconds of automated recovery. The diagnosis-first architecture proved effective across all four identified failure categories, confirming that targeted remediation outperforms uniform locator replacement when most instability originates outside the selector layer.